THE INFLUENCE OF TILT ANGLE ON THE PERFORMANCE OF SOLAR PANELS AS A SMART HELMET POWER SUPPLY IN A MOTORCYCLE SAFETY SYSTEM - Muhammad Sekal Maulidan; Rahmat Hidayat; Ridwan Satrio Hadikusuma; Ibrahim Lammada (TEKNOKOM, 2022)
The performance of a solar panel module is strongly influenced by its orientation and tilt angle. Tests have been carried out to track variations in the performance of the solar panel module and electrical parameters at various angles of inclination in the conditions of Karawang and Bogor. There are two experimental modes: 1) a varying slope module under a constant irradiance level, 2) a varying irradiation intensity at the optimal tilt setting. For the former schematic, the irradiation levels were carried out at 2 different locations, and for the later setup, the angle of inclination of the module was varied from 90° and 180° by using a single axis tracer At 90° tilted angle in Karawang test place at rest condition, morning experiment give the result of 5,69V on average while in Bogor the experiment gives 5,46V on average. At 180° tilted angle in Karawang test place at rest condition, morning experiment give the result of 5,49V on average while in afternoon experiment afternoon 3.026V on average. In Bogor test place morning experiment give solar panel 5,2V on average and 3,33V at afternoon experiment. In the electrical parameters of the module, the open circuit voltage, short circuit current, maximum power point voltage and maximum power point current decrease substantially with increasing slope angle, while the charge factor decreases somewhat gradually. Tests in both Karawang and Bogor in the afternoon and afternoon confirmed that the optimal tilt angle on cloudy on  with UV index between 1-2 in the morning and 3-4 in the afternoon on average is 180° tilted and directing the solar panel module at this angle will maximize the captured solar energy and thereby improve its performance.